Genome maintenance during embryogenesis - Munisha, M.; Schimenti, J. C.
Genome maintenance during embryogenesis is critical, because defects during this period can be perpetuated and thus have a long-term impact on individual's health and longevity. Nevertheless, genome instability is normal during certain aspects of embryonic development, indicating that there is a balance between the exigencies of timely cell proliferation and mutation prevention. In particular, early embryos possess unique cellular and molecular features that underscore the challenge of having an appropriate balance. Here, we discuss genome instability during embryonic development, the mechanisms used in various cell compartments to manage genomic stress and address outstanding questions regarding the balance between genome maintenance mechanisms in key cell types that are important for adulthood and progeny.
Keywords: EMBRYONIC DEVELOPMENT; GENOME INSTABILITY; ANEUPLOIDY; GENOME MAINTENANCE; GERMLINE; STEM CELLS